Co-construcción de soluciones barriales participativas, caso de estudio: Barrio Miraflores Bajo, parroquia Sucre, cantón y provincia de Loja, periodo abril-septiembre 2022 - Ochoa Aguirre, Jessica Estefanía (2023)
The project of Co-Construction of Participatory Neighborhood Solutions, study case of "Miraflores Bajo" neighborhood, was oriented towards creating a positive contribution to the neighborhood by carrying out participatory and collaborative processes in the residents, seeking for solutions to problems, involving public institutions , authorities and citizens, carrying out an adequate management to find solutions that must be studied for their subsequent execution. In order to achieve the Co-construction of neighborhood solutions, several activities were developed, seeking to promote participation and neighborhood organization, reactivate the board of directors and commit them to the present Project. In addition existing problems were also diagnosed, among the main ones were found: the insecurity that afflicts the residents, the non-existence of a physical space for meetings, the lack of maintenance and improvement of places for public use such as multiple-use courts; to then proceed together with the residents to build possible effective solutions to the problems encountered by drawing up an action plan. Likewise, a lack of citizen participation and collaboration on the part of the residents of the neighborhood was perceived, thus making it difficult to carry out the project. On the other hand, for its execution, the action research methodology was used, with a mixed nature, using qualitative and quantitative tools, in terms of the qualitative one, the observation sheet was used, which allowed the collection of non-numerical data, and in the quantitative one, the same survey that was carried out on 109 inhabitants of the neighborhood and helped in the collection of numerical data.